Akibat Hukum Terhadap Akta Wasiat Yang Tidak Diketahui Para Ahli Waris Dan Penerima Wasiat Setelah Pembagian Harta Waris Berdasarkan Hukum Waris Barat - Monica Belinda Oksavina; Husni Kurniawati (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
A Will (testament) is a legal instrument containing a person’s declaration regarding what he or she wishes to take effect after death, and it may be revoked by the testator at any time. In practice, a testator often does not inform family members or even beneficiaries of the existence of a will, with the expectation that upon death the will shall be implemented and the estate distributed in accordance with its provisions. This study examines the legal consequences of a will that is unknown to the heirs and beneficiaries after the distribution of the estate has been carried out, as well as the measures that must be undertaken prior to the execution of inheritance distribution. This research employs a normative juridical research method with a statutory approach. A will that is unknown to the heirs remains valid and retains its legal force. Where the distribution of inheritance is not based on an existing will, such distribution may prejudice the beneficiaries designated in the will. Consequently, the beneficiaries are entitled to assert their rights against the heirs and may demand a redistribution of the inheritance in accordance with the will. The procedure that must be undertaken prior to the distribution of inheritance is the verification of the existence of a will through the Central Register of Wills, which may be facilitated by a Notary by complying with the procedures stipulated in the Regulation of the Minister of Law of the Republic of Indonesia No. 16 of 2025.